Cancer-testis antigens in ovarian cancer: implication for biomarkers and therapeutic targets - Kaipeng Xie; Chenyang Fu; Suli Wang; Hanzi Xu; Siyu Liu; Yang Shao; Zhen Gong; Xiaoli Wu; Bo Xu; Jing Han; Juan Xu; Pengfei Xu; et al. (BMC, 2019)
Abstract Ovarian cancer remains the most fatal gynecologic malignancy worldwide due to delayed diagnosis as well as recurrence and drug resistance. Thus, the development of new tumor-related molecules with high sensitivity and specificity to replace or supplement existing tools is urgently needed. Cancer-testis antigens (CTAs) are exclusively expressed in normal testis tissues but abundantly found in several types of cancers, including ovarian cancer. Numerous novel CTAs have been identified by high-throughput sequencing techniques, and some aberrantly expressed CTAs are associated with ovarian cancer initiation, clinical outcomes and chemotherapy resistance. More importantly, CTAs are immunogenic and may be novel targets for antigen-specific immunotherapy in ovarian cancer. In this review, we attempt to characterize the expression of candidate CTAs in ovarian cancer and their clinical significance as biomarkers, activation mechanisms, function in malignant phenotypes and applications in immunotherapy.